2016
DOI: 10.1590/s0100-204x2016000300001
|View full text |Cite
|
Sign up to set email alerts
|

Conservação de caqui 'Fuyu' com o tratamento em pré-colheita e pós-colheita com 1-metilciclopropeno

Abstract: Resumo -O objetivo deste trabalho foi comparar os efeitos da pulverização pré-colheita de 1-metilciclopropeno aquoso (1-MCPa) e tratamento pós-colheita de 1-metilciclopropeno gasoso (1-MCPg) sobre a maturação e a qualidade de caqui (Diospyros kaki) 'Fuyu'. Pulverizaram-se 150 mg L -1 de 1-MCPa nas plantas, na primeira semana de colheita comercial. Os frutos foram colhidos aos 1, 7, 14 e 21 dias, após a pulverização do 1-MCPa (DAAM), e tratados ou não com 0,6 µL L -1 de 1-MCPg, um dia após a colheita. Os tratam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Resultados inferiores aos encontrados por Vieites et al (2012), que obtiveram valores médios, para sólidos solúveis, variando entre 15 e 21 ºBrix em seu trabalho sobre a influência de radiação gama em caquis 'Giombo'. Vieira et al (2016) observaram acréscimo no teor de sólidos solúveis ao longo do armazenamento de caqui 'Fuyu' tratado com 1-metilciclopropeno, variando de 13,6 a 17,4 ºBrix durante o experimento, sendo este comportamento e seus valores mais próximos aos apresentados neste trabalho.…”
Section: Resultsunclassified
“…Resultados inferiores aos encontrados por Vieites et al (2012), que obtiveram valores médios, para sólidos solúveis, variando entre 15 e 21 ºBrix em seu trabalho sobre a influência de radiação gama em caquis 'Giombo'. Vieira et al (2016) observaram acréscimo no teor de sólidos solúveis ao longo do armazenamento de caqui 'Fuyu' tratado com 1-metilciclopropeno, variando de 13,6 a 17,4 ºBrix durante o experimento, sendo este comportamento e seus valores mais próximos aos apresentados neste trabalho.…”
Section: Resultsunclassified
“…The obtained results show that the combination of pre-and postharvest 1-MCP application optimizes the fruit capacity to retain ripening and reduce the incidence of disorders during cold storage, resulting in a higher fruit firmness as well as longer ethylene suppression. In persimmon, only a study on the cultivar 'Fuyu' compared the effects of pre-and post-MCP treatments on the fruit quality during maturity, and positive results were found with the pre-MCP application [10].…”
Section: Discussionmentioning
confidence: 99%
“…In persimmon, information about the effect of preharvest 1-MCP application is scarce. Only one study about the 'Fuyu' cultivar has reported a positive effect of this treatment on retarding fruit maturity on trees [10].…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet quality demanded standards from the consumer market, there is a need to expand the research field for knowledge regarding persimmon cropping, including aspects ranging from nutrition, irrigation and plants" canopy handling to before and after harvest studies (Biasi et al, 2007;Souza et al, 2011;Vieira et al, 2016), considering that these factors might be affected by growing"s location and chosen crop. The fruit farm, for instance, when led according to different growth stages, allows strategies and decisions to be defined beforehand, which contributes to improving the crops" efficiency and yield (Corsato et al, 2005).…”
Section: )mentioning
confidence: 99%